Genetic analysis of human papillomavirus type 11 isolates from patients with recurrent respiratory papillomatosis treated at Universitas Academic Hospital - Thuynsma, Corne (University of the Free State, 2021)
Human papillomavirus type 11 (HPV11) is a causative agent of recurrent respiratory papillomatosis (RRP), a common benign laryngeal neoplasm that presents mainly in children. The genome comprises three regions: the early region (E1, E2, E4, E5a/b, E6 and E7), the late region (L1 and L2), and the upper regulatory region (URR). A sequence-based classification system is primarily used to genotype HPV. The L1 is used for HPV type discrimination, and in combination with the URR, can be used to differentiate between various lineages. However, optimal sub-lineage classification requires whole genome sequencing (WGS). A recent study investigating the genomic diversity of globally circulating HPV11 isolates identified a novel lineage and two novel sub-lineages. It has been proposed that phylogenetic tree topologies using the sequences of concatenated E5a/b- L1-URR genes, a 208bp segment of the E2 gene, and the complete genome generates similar tree topologies. Also, there is currently no published data on the HPV11 intratypic variants circulating in the Free State region. Hence, this study investigated HPV11 intratypic variants circulating in patients with RRP at the Universitas Academic Hospital, and aimed to identify novel (sub)lineages through phylogenetic investigations. The study population included patients diagnosed with RRP caused by HPV11, and sequence data for geographically distinct HPV11 (sub)lineage representatives. The genetic variation of HPV11 isolated from patients with RRP was determined by sequencing the E5a/b, L1, URR and a segment of E2 genes. Four isolates of interest were selected for whole-genome sequencing and phylogenetically analysed to determine the presence of potentially novel isolates. Many nucleic heterogeneities and non-synonymous substitutions were identified in isolates characterised in this study. Phylogenetic analysis of the concatenated L1-URR and E5a/b-L1-URR resolved into lineages A and B; however, sub-lineage classification was unclear. Analysis of the complete genome determined the presence of a lineage B isolate and two isolates of interest. Comparative analysis of genetic variability determined that the concatenated E5a/b-L1-URR could not reliably classify isolates. A segment of the E2 gene could reliably distinguish between all lineages and sub-lineages, suggesting that this gene segment contains stable sub-lineage specific single nucleotide polymorphisms (SNPs) and may serve in sub-lineage identification. In conclusion this study provides the most comprehensive data on the genomic diversity of HPV11 in the Free State to date. Results obtained in the current study support WGS for HPV11 classification below lineage level as a standard, as it generates more information regarding genetic variants.
Dissertation (M.Sc. (Medical Microbiology and Virology))--University of the Free State, 2021
Keywords: Human papillomavirus type; Nucleotide polymorphisms; Genotype HPV; Phylogenetic investigations